2019
DOI: 10.1017/s1366728919000051
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual versus monolingual infants’ novel word-action mapping before and after first-word production: Influence of developing noun-dominance on perceptual narrowing

Abstract: This experimental study examined bilingual (English and another noun-dominant language) and monolingual (English) preverbal (10.5-month-old) and postverbal (12.5-month-old) infants’ word-action mapping. Sixteen infants in each group were habituated to dynamic video-displays of novel word-action pairings during infant-controlled habituation. They received two words, /wem/ and /bæf/, spoken synchronously with an adult shaking or looming an object, and were tested with switched versus same word-action pairings. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(90 reference statements)
1
1
0
Order By: Relevance
“…The unexpected finding in the current study was that bilingual children showed worse word-learning performance than monolingual children. This finding, although unusual within the broader literature, is consistent with recent evidence suggesting that monolingual children can outperform bilingual children on some word-learning tasks (Gogate & Maganti, 2020; Kalashnikova, Escudero & Kidd, 2018). Besides SES discrepancies between groups – a factor we have taken into account in our analyses – we considered a number of possible explanations for this finding.…”
Section: Influence Of Eye-gaze On Novel-word Retentionsupporting
confidence: 90%
See 1 more Smart Citation
“…The unexpected finding in the current study was that bilingual children showed worse word-learning performance than monolingual children. This finding, although unusual within the broader literature, is consistent with recent evidence suggesting that monolingual children can outperform bilingual children on some word-learning tasks (Gogate & Maganti, 2020; Kalashnikova, Escudero & Kidd, 2018). Besides SES discrepancies between groups – a factor we have taken into account in our analyses – we considered a number of possible explanations for this finding.…”
Section: Influence Of Eye-gaze On Novel-word Retentionsupporting
confidence: 90%
“…For instance, these prior studies tested 2- and 3-year-olds whereas we tested 4-and 5-year old children. It is possible that effects of bilingualism on sensitivity to eye-gaze during learning may show up more readily in younger children (e.g., Gogate & Maganti, 2020), who have less robust vocabulary and cognitive skills.…”
Section: Influence Of Eye-gaze On Novel-word Retentionmentioning
confidence: 99%